Peel's other repeal: the Test and Corporation Acts, 1828 - Gaunt, Richard A. (Wiley, 2014)
This article considers Robert Peel’s role in the repeal of the Test and Corporation Acts in 1828. Traditionally overshadowed by the larger campaign to secure catholic emancipation in 1829, the repeal legislation assumes importance in Peel’s political career for three reasons. It was Peel’s first major challenge as leader of the house of commons in Wellington’s ministry; his handling of the issue revealed all his strengths and weaknesses in the role. Peel’s insistence on the active participation of the anglican Church hierarchy in passing repeal with appropriate safeguards (through a declaration to be taken by the majority of officeholders) foreshadowed his later tactics in settling contentious Church issues by negotiation with the Church’s leaders (leading to the formation of the Ecclesiastical Commission in 1835). The success of Russell’s original repeal motion challenged the expectation (shared by Peel) that repeal would follow, rather than precede, emancipation. The necessity of confronting repeal head-on formed a backdrop to that ‘ripening’ of Peel’s views which commentators and historians have detected during this period.